Tourist Perceptions On Supporting Infrastructure Facilities And Climate-Based Visiting Time Of Ngebel Lake, Ponorogo - Ayu Prasetyowati, Ardhila; Harahab, Nuddin; Soemarno, Soemarno (Graduate School, Universitas Brawijaya, 2014)
This study aims to analyze the tourists' perception about the importance and satisfaction on the product of fisheries tourism, and to assess the visiting time of tourist based on climate conditions. The research was conducted in May to June 2013 in Ngebel Lake, Ponorogo. We used descriptive quantitative approach, with 45 respondents. Data collected from interview, questionnaire and observation. Analytical methods were used to determine the perception of tourists on the satisfaction and interest in fisheries tourism products, i.e. Importance Performance Analysis (IPA). We also used Tourism Climate Index (TCI) to determine the visiting time of tourist. The results show the value of satisfaction and tourist interest is low, therefore the improvement of several aspects become important. It is encompasses: a) the existence of parking area; b) the condition of Ngebel Lake; c) planning and management system, the condition of the local community; and d) activities of fish course restaurant and fish farming system of floating net cages. TCI value indicates ideal conditions for tourists traveled in Ngebel Lake is in November (convenience index value of 106), in December (97) and in April (94). This appropriate time to visit Ngebel Lake is expected to create a good impression for the tourists and enjoy the various fisheries activities in Ngebel Lake. Keywords: Importance Performance Analysis, Ngebel Lake, Tourist Climate Index